2017
DOI: 10.17219/acem/67563
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy of hepatocellular carcinoma in rats: Detection of cell homing and tumor mass by magnetic resonance imaging using iron oxide nanoparticles

Abstract: Background. Bone marrow-derived mesenchymal stem cells (MSCs) are reported to improve hepatic fibrosis, and may impact the signaling mechanisms leading to the induction of hepatocellular carcinoma (HCC) in animal models of liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…In vivo tracking of stem cells using SPIONs has already been extensively studied in several animal models. For example, labeled MSCs were tracked in liver having hepatocellular carcinoma using MRI [42]. In another study, after transplantation of SPION-labeled MSCs in rats via the portal veins, they were visualized by MRI showing the improvement in the hepatic pathology and diminishing the cirrhosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo tracking of stem cells using SPIONs has already been extensively studied in several animal models. For example, labeled MSCs were tracked in liver having hepatocellular carcinoma using MRI [42]. In another study, after transplantation of SPION-labeled MSCs in rats via the portal veins, they were visualized by MRI showing the improvement in the hepatic pathology and diminishing the cirrhosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was performed in the Stem Cell Unit according to a previously published method [17]. MSCs were extracted and suspended in 25 cm 2 cell culture flasks (Corning, Corning, NY, USA) in DMEM media containing 10% FBS and supplemented with antibiotics (100 U/mL penicillin/streptomycin (Gibco, Life Technology, Carlsbad, CA, USA)) [15].…”
Section: Methodsmentioning
confidence: 99%
“…These cells were confirmed to be MSCs by flow cytometry (FACSAria III cell sorter model no. 6482-35, BD Bioscience, Erembodegem, Belgium) for detection of CD29 + /CD45 − cells [17]. For the gene expression studies, stem cells were seeded at a density of 3 × 10 5 cells/well in a 6-well cell culture plate.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, similar results by Lai and co-authors have shown that MSCs that overexpress human hepatocyte growth factor (HGF) promote liver recovery in a rat liver fibrosis model [120]. Further, labeling of MSC with NP led to an accumulation of the cells in MRI-based imaging [119,120], which seems to confirm the idea that magnetic NPs in liver fibrosis can be used as a diagnostic agent for MRI.…”
Section: Theoretical Background Of Magnetismmentioning
confidence: 52%
“…Labeling of MCS with MNPs can be used as a supplementary diagnostic approach. Recently, Faidah at al., proved that application of MNPs have not changed the viability and proliferative capabilities of MSCs in a rat cirrhosis model based on a carbon tetrachloride (CCl 4 ) model for toxic liver injury [119]. Additionally, similar results by Lai and co-authors have shown that MSCs that overexpress human hepatocyte growth factor (HGF) promote liver recovery in a rat liver fibrosis model [120].…”
Section: Theoretical Background Of Magnetismmentioning
confidence: 99%